Attentional processing of food pictures in individuals with Anorexia Nervosa: an eye-tracking study - Giel, Katrin; Friederich, Hans-Christoph; Teufel, Martin; Hautzinger, Martin; Enck, Paul; Zipfel, Stephan (Biological psychiatry, 2011)
Background - Etiologic models of anorexia nervosa (AN) suggest that cognitive factors play a crucial role in the disorder's psychopathology. Attentional aspects of food processing in AN remain largely unknown. Both an early attentional bias (vigilance) and inattentiveness (avoidance) to food pictures have been reported in patients with eating disorders. The study's aim was to examine the vigilance-avoidance hypothesis concerning food information processing by unraveling the time course of attention deployment in individuals with AN. - Methods - We used eye-tracking to examine continuous attention deployment in 19 individuals with AN during free visual exploration of food pictures versus nonfood pictures compared with 18 fasted and 20 nonfasted healthy control subjects. - Results - Compared with healthy control subjects, AN patients allocated overall less attention to food pictures but showed no early attentional bias toward food pictures. Attentional engagement for food pictures was most pronounced in fasted healthy control subjects. The extent of attention deployment in AN patients was associated with indicators of the disorder's severity. - Conclusions - Gaze data suggest that individuals with AN show no early vigilance but later avoidance when confronted with food information. This suggests that initially, AN patients perceive incentive salience from food information because they process food pictures in the same way healthy control subjects do. The time course of attention deployment suggests that it is only after a first phase of stimulus encoding and labeling as food that individuals with AN avoid food pictures. This pattern of attention deployment is probably mediated by disorder-specific dysfunctional cognitions.
Available online 3 December 2010
Gesehen am 22.06.2022